Bleeding symptoms in patients diagnosed as type 3 von Willebrand disease: Results from 3WINTERS‐IPS, an international and collaborative cross‐sectional study. (25th August 2020) - Tosetto, Alberto; Badiee, Zahra; Baghaipour, Mohammad‐Reza; Baronciani, Luciano; Battle, Javier; Berntorp, Erik; Bodó, Imre; Budde, Ulrich; Castaman, Giancarlo; Eikenboom, Jeroen C. J.; Eshghi, Peyman; Ettorre, Cosimo; et al.
Abstract: Background: Type 3 von Willebrand's disease (VWD) patients present markedly reduced levels of von Willebrand factor and factor VIII. Because of its rarity, the bleeding phenotype of type 3 VWD is poorly described, as compared to type 1 VWD. Aims: To evaluate the frequency and the severity of bleeding symptoms across age and sex groups in type 3 patients and to compare these with those observed in type 1 VWD patients to investigate any possible clustering of bleeding symptoms within type 3 patients. Methods: We compared the bleeding phenotype and computed the bleeding score (BS) using the MCMDM‐1VWD bleeding questionnaire in patients enrolled in the 3WINTERS‐IPS and MCMDM‐1VWD studies. Results: In 223 unrelated type 3 VWD patients, both the BS and the number of clinically relevant bleeding symptoms were increased in type 3 as compared to type 1 VWD patients (15 versus 6 and 5 versus 3). Intracranial bleeding, oral cavity, hemarthroses, and deep hematomas were at least five‐fold over‐represented in type 3 VWD. A more severe bleeding phenotype was evident in patients having von Willebrand factor antigen levels < 20 IU/dL at diagnosis in the two merged cohorts. In type 3 patients, there was an apparent clustering of hemarthrosis with gastrointestinal bleeding and epistaxis, whereas bleeding after surgery or tooth extraction clusters with oral bleeding and menorrhagia. Conclusions: In the largest cohort of type 3 VWD patients, we were able to describe a distinct clinical phenotype that is associated with the presence of a more severe hemostatic defect.